Evaluasi Kinerja Struktur Tahan Gempa Dengan Metode Pushover Analysis Pada Gedung RS. Muhammadiyah Siti Khodijah Gurah - Kediri - Abdul kholil; Titin Sundari; Meriana Wahyu Nugroho; Rahma Ramadhani (Fakultas Teknik Universitas Cenderawasih, 2023)
Indonesia is a country that is vulnerable to natural disasters, one of which is an earthquake. Because Indonesia is at the meeting point of the 3 most important major plates in the world, one of the effects of the earthquake is damage to building structures. Structural planning is needed for buildings with earthquake resistance from the many occurrences of earthquakes seen in recent times and the losses incurred.Pushover analysis is a non-linear static analysis. The static load captured at the center of mass of each floor is taken into account in this pushover analysis as the effect of the design earthquake on the building structure, the aim of which is to find out how the building structure will collapse during an earthquake so that you can know which parts of the structure are in critical condition and what to do if they do not meet the requirements.The results of the analysis show that the maximum base shear force for the x direction capacity curve is 484.6749 tons with a displacement of 0.095228 m occurring in the 6th step, while the y direction of the maximum base shear force is 555.339 tons and displacement of 0.152807 m occurs in the 14th step. The performance point value is also obtained from the analysis pushover in the x direction with = 475.025 tons and D = 0.087 m yield Sa = 0.205 g and Sd = 0.072 m, while for the y direction with = 499.168 tons and D = 0.086 m yield Sa= 0.225 g and Sd = 0.067 m. Then at the level of building performance in the x and y direction parametersMaximum Total Drift Ratio included in the category Immediate Occupancy (IO), it can be concluded that the building did not suffer significant damage, the building is safe when an earthquake occurs, the risk of loss of life and structural failure is not too significant and can be used again immediately.